Radiological assessment of anal cancer: an overview and update. Issue 1 (December 2016) - Granata, Vincenza; Fusco, Roberta; Reginelli, Alfonso; Roberto, Luca; Granata, Francesco; Rega, Daniela; Rotondo, Antonio; Grassi, Roberto; Izzo, Francesco; Petrillo, Antonella
Abstract Anal cancer is uncommon neoplasm with an incidence of 2 new cases per 100, 000 per year in the USA, accounting approximately 0.4 % of all tumors and 2.5 % of gastrointestinal malignancies. An early detection of the anal cancer is crucial for the patient management, whereas the diagnosis at an early stage allows conservative management with sphincter sparing, on the contrary a delays in diagnosis might lead to an advance cancer stage at presentation with worst survival. According to National Comprehensive Cancer Network (NCCN) Anal Carcinoma guidelines the patients should be subjected to a careful clinical examination, including a digital rectal examination (DRE), an anoscopic examination, and palpation of inguinal nodes. The guidelines recommended for the assessment of T stage, only a clinical examination, while the role of imaging techniques, as Magnetic Resonance imaging (MRI) is limited to the identification of regional nodes. Instead, the endoanal ultrasound (EAUS) is not recommended. This paper presents an overview and some updates about 3D EAUS and MRI in detection, staging and assessment post therapy of anal cancer patients.